2021
DOI: 10.31098/ijcbm.v1i1.3881
|View full text |Cite
|
Sign up to set email alerts
|

Workplace Spirituality as a Mediator to Individual Spirituality and Organizational Performance in a Hospitality Business: An Evidence from Hotel X, Clarkfield, Angeles City, Pampanga, Philippines

Abstract: Through this study, we want to determine whether workplace spirituality has mediating effects between individual's spirituality and organizational performance in a hospitality business in Hotel X, Clarkfield, Angeles City, Pampanga, Philippines. We used the Spirituality Assessment Scale developed by Hamilton Beazley, PhD targeting one hundred twenty-nine respondents. As far as we have known, our study may serve as one of the pioneering studies of spirituality in the hospitality industry. Overall, hotel employe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 8 publications
1
2
0
Order By: Relevance
“…However, studies with and without the control variables (Caesens et al, 2019) showed identical results. This result confirms similar findings from few related studies, particularly on job performance in the extant literature (Biswakarma, 2018;Iksan et al, 2020;Jena, 2021;Salcedo & Lazatin, 2021;Tayebiniya & Khorasgani, 2018). The observation that workplace spirituality enhancing POS and job performance outcomes showed that workplace spirituality experience represents many positive experiences such as recognition, organizational identification, and social support that have implications for desirable organizational outcomes.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…However, studies with and without the control variables (Caesens et al, 2019) showed identical results. This result confirms similar findings from few related studies, particularly on job performance in the extant literature (Biswakarma, 2018;Iksan et al, 2020;Jena, 2021;Salcedo & Lazatin, 2021;Tayebiniya & Khorasgani, 2018). The observation that workplace spirituality enhancing POS and job performance outcomes showed that workplace spirituality experience represents many positive experiences such as recognition, organizational identification, and social support that have implications for desirable organizational outcomes.…”
Section: Discussionsupporting
confidence: 90%
“…Workplace spirituality significantly affects job performance (Biswakarma, 2018;Iksan et al, 2020;Jena, 2021). Employee's spirituality, workplace spirituality, and perceived organizational performance move in the same direction (Salcedo & Lazatin, 2021).…”
Section: Workplace Spirituality and Job Performancementioning
confidence: 98%
“…Business lessons are becoming more precise, with many students seeking extracurricular practices and taking additional classes to learn how to win business ( Hitka et al., 2021 ). The critical role of the academy in introducing spirituality has returned to its rightful place and is exerting considerable influence inside and outside the university walls ( Salcedo and B Lazatin, 2021 ). Higher education institutions help students build better relationships after college and prepare for long-term success.…”
Section: Introductionmentioning
confidence: 99%